2018
DOI: 10.26515/rzsi/v118/i1/2018/122305
|View full text |Cite
|
Sign up to set email alerts
|

First Report of <I>Drupella cornus</I> Röding, 1798 (Gastropoda: Muricidae), a Biological Indicator of Coral Reef Habitat of Lakshadweep Archipelago, India

Abstract: The present study infers that the impact of Drupella cornus Röding, 1798, particularly on the coral, Pocillopora verrucosa (Ellis and Solander, 1786) at Minicoy Island, Lakshadweep Archipelago, India. During the benthic reef monitoring in connection with the health of the reef ecosystem under Tourism Capacity Building project, it was identified as one of the biological indicators of the reef habitat. Further, the description and morphometric characters of the species were studied and presented in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Sites were randomly selected according to accessibility and surveyed by snorkelling between 0 and 5 m, in accordance with other studies that found Drupella spp. mainly in the shallower reefs (Taylor, 1978;Turner, 1994a;Cumming, 2009a, b;Hoeksema et al, 2013;Bruckner et al, 2017;Koido et al, 2017;Scott et al, 2017a, b;Hamman, 2018;Marimuthu & Tripathy, 2018). To evaluate density variation within and among sites, belt transects of 200 m 2 (50 9 4 m each) were conducted both on the reef flat (6 transects at 0-2 m) and along the reef crest (6 transects at 2-5 m) in each site.…”
Section: Biological and Environmental Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sites were randomly selected according to accessibility and surveyed by snorkelling between 0 and 5 m, in accordance with other studies that found Drupella spp. mainly in the shallower reefs (Taylor, 1978;Turner, 1994a;Cumming, 2009a, b;Hoeksema et al, 2013;Bruckner et al, 2017;Koido et al, 2017;Scott et al, 2017a, b;Hamman, 2018;Marimuthu & Tripathy, 2018). To evaluate density variation within and among sites, belt transects of 200 m 2 (50 9 4 m each) were conducted both on the reef flat (6 transects at 0-2 m) and along the reef crest (6 transects at 2-5 m) in each site.…”
Section: Biological and Environmental Data Collectionmentioning
confidence: 99%
“…were reported from a wide range of regions including Kenya (McClanahan, 1994), Western Australia (Ayling & Ayling, 1987), Hong Kong (Cumming, 1998;Morton and Blackmore, 2009), Red Sea (Antonious, A. & B. Riegel, 1998), Thailand (Scott et al, 2017a, b) and India (Marimuthu & Tripathy, 2018). These events appeared to be caused by overfishing of natural predators, high coral mortality and changes in temperature and salinity (Turner, 1994a, b;Cumming, 2009a, b), although the causes are complex and still not completely understood (McClanahan, 1994(McClanahan, , 1997Lam & Shin, 2007;Ratianingsih et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Information is lacking on the species description and the interaction of Drupella cornus on coral species from the Indian coastal region. Marimuthu and Tripathy (2018) reported this species for the first time as a biological indicator of the coral reef habitat of Lakshadweep Archipelago. Antonius and Riegl (1997) reported the outbreak of coral disease caused by this species.…”
Section: Discussionmentioning
confidence: 98%
“…Misalnya, anggota Potamididae yang umum diketahui merupakan kelompok penghuni mangrove (Reid et al, 2008;Mujiono, 2009;Merly & Saleky, 2021). Di antara kelompok pengunjung dan fakultatif, di antaranya: anggota Trochidae yang umum dikenal sebagai gastropoda laut dan terumbu (Williams et al, 2010;Yamamori & Kato, 2018); serta Littorinidae yang sebagian besar dikenal sebagai keong laut dan Neritidae euryhaline dan merupakan gastropoda perairan umum (tawar) dan payau berlumpur (Symanowski & Hildebrandt, 2010;Abdou et al, 2015); Juga, euryhaline lainnya, Nassariidae, yang pada habitat sedimen laut dan payau (Iannotta et al, 2009); Anggota Muricidae yang dikenal sebagai gastropoda laut pada habitat terumbu (Pappalardo et al, 2014;Marimuthu & Tripathy, 2018); Serta, anggota Ellobioidea yang dikenal sebagi siput yang sangat beragam secara morfologi dan secara ekologis menempati habitat yang lebar, yaitu darat, laut dan payau (Weigand et al, 2013).…”
Section: Pembahasanunclassified